Reinventing employee morale during Covid Pandemic: Study of psychological contract and job satisfaction of healthcare professionals - Fazeelath Tabasum; Nitu Ghosh (Goodwood Publishing, 2021)
Purpose: The purpose of the study is to comprehend and appraise the impact of employee morale during the COVID pandemic on psychological contract and job satisfaction of healthcare professionals in Indian private Hospitals. Research methodology: The study adopted an empirical analysis. A structured questionnaire was adopted based on the Scale for assessing psychological contract by Rousseau (2000) for collecting primary data through a survey from doctors and nurses in selected private hospitals. Results: The results suggest that managing the healthcare system by focusing on the insight of employee psychological contract and job satisfaction can improve employee morale during crisis conditions like the COVID-19 pandemic among the doctors and nurses in the healthcare sector. Limitations: Due to COVID 19 pandemic, it was difficult to get responses from healthcare professionals. Contribution: This paper aims to support the healthcare sector by recommending the building of employee morale and fulfilling the psychological contract to achieve job satisfaction of healthcare professionals in the healthcare sector.